Prosthesis position and its influence on complications after transcatheter aortic valve implantation with self-expanding valves. (14th October 2021) - Breitbart, P; Minners, J; Hein, M; Schroefel, H; Neumann, F J; Ruile, P
Abstract: Background/Introduction: Prior studies in patients with transcatheter aortic valve implantation (TAVI) demonstrated an influence of transcatheter heart valve (THV) position on the occurrence of new conductions disturbances (CD) and paravalvular leakage (PVL) post TAVI in balloon-expandable valves (BEV). Purpose: Purpose of this study was to investigate the THV position and its influence on the occurrence of CD and PVL in self-expanding valves (SEV). Methods: We performed fusion imaging of pre- and post-procedural computed tomography angiography in 104 TAVI-patients (all with Evolut R) to receive a 3-D reconstruction of the THV within the native annulus region. The THV length below the native annulus was measured for assessment of implantation depth. Electrocardiograms pre-discharge were assessed for conduction disturbances (CD), PVL was determined in transthoracic echocardiography. Results: The mean implantation depth of the THV in the whole cohort was 4.3±3.0 mm. Using the best cut-off of >4 mm in receiver operating characteristic curve analysis (sensitivity 83.3%, specificity 60.0%) patients with lower THV position developed more new CD after TAVI (68.2 vs. 23.7%, P<0.001). A deep THV position was identified as the only predictor for new CD after TAVI (odds ratio [CI]: 1.312 [1.119–1.539], P=0.001). The implantation depth showed no influence on the grade of PVL (r=0.052, P=0.598). Conclusions: In patients with TAVI using the Evolut R SEV, a lower THV positioning (>4 mm length below annulus) was a predictor for new conduction disturbances. In contrast, prosthesis position was not associated with the extent of PVL. Funding Acknowledgement: Type of funding sources: None.